The Emperor's Revenge - Cussler, Clive; Morrison, Boyd 1967-; Brick, Scott; Penguin Audio (Firm) (New York : Penguin Audio, 2016)
Juan Cabrillo and the crew of the Oregon face their toughest challenge yet when a violent bank heist during the Monaco Grand Prix decimates the Corporation's accounts. To get the money back, Juan joins forces with an old friend from his days in the CIA so they can track down a rogue hacker and a ruthless former Ukrainian naval officer.
Keywords: Cabrillo, Juan (Fictitious character) -- Fiction; Hackers -- Fiction; Financial crises -- Fiction; Audiobooks; Thrillers (Fiction); Audiobooks